Marketing Mechanism of Children’s Nutrition in General Secondary Education Institutions - Anastasiia Konovalenko (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The relevance of the study of the organisation and quality of children's nutrition in educational institutions is related to the need to determine the potential for applying marketing approaches to improve the level of child nutrition organisation. The purpose of the study is to identify methodological approaches for the establishment of a conceptual model of the marketing mechanism for organising children's nutrition in institutions of general secondary education. The theoretical and methodological basis of the study was general scientific and specific methods, with the help of which the theoretical provisions of the directions of the problem of organising children's nutrition in institutions of general secondary education were formulated. The study analyses the internal structure of the marketing mechanism by considering its main functions: planning, organisation, motivation, and control. The content of the key functions of the marketing mechanism is revealed and their content is characterised, and a conceptual model of the marketing mechanism for organising food for school-age children is developed based on the interaction of marketing entities at the social, systemic and personal levels of management. The study suggests considering the core of the marketing mechanism model as a system of interaction between marketing entities that are key stakeholders in the market of food and nutrition services for school-age children. It is established that the strategic priority of introducing a marketing mechanism for organising children's nutrition is to promote the comprehensive implementation of long-term programmes in this area based on public-private partnerships. The practical value of the study is conditioned by a comprehensive analysis of the structure of the marketing mechanism aimed at organising interaction between the subjects of the process, which would contribute to achieving the maximum possible level of quality and safety of children's nutrition under existing conditions